محددات النمو الاقتصادي لبلدان الخليج العربي للفترة 1993-2013 باستخدام بيانات الدمج - الزوبعي, عبيد محمود محسن; اليساري, حاتم هاتف عبد الكاظم; عبدالوهاب, سمير عبد الجبار (Sulaimani Journal for Humanities, 2022)
Statistical data play an important role in analyzing the different phenomena in the human societies, especially the economic phenomenon which focus on macroeconomic issues. The results of this type of studies provide valuable information for the decision makers in the political and economical aspects.Type of data available for the researcher determines the econometric model, which should be used. One type of the data is the panel data. There are three common models for analyzing panel data: Fixed effect mode, random effect model, and the Pooled Ordinary least squares model. This study is an attempt to determine the sources of economic growth in the countries of the Arab Gulf Corporation, during the period 1993-2013. The main findings of the study are that the pattern of growth in the Gulf countries is still dependent on the intensive use of conventional production factors. The most important factor in economic growth is capital.. The most important recommendations that can be raised is the need to pay attention to the training of workers and expand the current employment policies. The results also suggest an expansion in investment as a factor in the economic growth of the Gulf Arab countries. The research focused on determining the most efficient model, through a comparison between five types of models, where the (two-way fixed effects model) was adopted.